The genus Ormosia Jacks. (Leguminosae, Papilionoideae) in the State of Guerrero, Mexico - Cruz-Durán, Ramiro; Jiménez-Ramírez, Jaime (Instituto de Ecología, A.C., 2015)
Ormosia carinata and O. oaxacana (Leguminosae, Papilionoideae, tribe Sophoreae) are recorded for the first time from the state of Guerrero, Mexico. Descriptions for both species, lists of specimens studied, a dichotomous key to distinguish both taxa, and an illustration of O. carinata are provided. Oromosia carinata was formerly known only from the regions of Los Tuxtlas and Uxpanapa in Veracruz and Oaxaca.